Dynamic Modeling and PID Control of a 6-DOF Robotic Arm Using ROS and Gazebo - Firdaus, Ahmad Riyad; Cyrillus Rudi Soru; Hendawan Soebhakti (Journal of Applied Electrical Engineering, 2025)
This paper presents the dynamic modeling and control evaluation of a six degrees-of-freedom (6-DOF) robotic manipulator. The manipulator was developed in the Robot Operating System (ROS) and Gazebo using a detailed URDF model with complete geometric and inertia parameters. Proportional–Integral–Derivative (PID) controllers were tuned through ROS dynamic reconfiguration and tested under four payloads: 0; 0,19; 0,39; and 0,50 kg. Controller performance was assessed using rise time, settling time, overshoot, and steady-state error. The results show stable responses across all conditions, with no overshoot and near-zero steady-state errors. Increasing payloads generally led to longer rise and settling times, while joints aligned with gravity exhibited faster responses under heavier loads. These findings confirm that properly tuned PID controllers can maintain robust and accurate manipulator performance and demonstrate the effectiveness of ROS–Gazebo as an open-source platform for robotic control experimentation and future integration of adaptive or AI-based methods.